Wage Setting Under Different Monetary Regimes - Steinar Holden (Center for Economic Studies and ifo Institute (CESifo), 2002)
In an economy with large wage setters (like industry unions), the monetary regime affects the trade-off between consumer real wages and employment and profits faced by the wage setters. This paper shows that an exchange rate target, including participation in a monetary union, is likely to involve lower wages in the traded sector, and higher wages in the non-traded sector, than does a price target. An exchange rate target also involves higher prices on non-traded goods relative to traded goods. Overall welfare is likely to be higher under a price target.
Keywords: 330; wage bargaining; monetary union; inflation target; monetary regime; equilibrium unemployment